Fish consumption is an indicator of exposure to non-dioxin like polychlorinated biphenyls in cumulative risk assessments based on a probabilistic and sensitive approach. (1st January 2021) - Lee, Ching-Chang; Chang, Wei-Hsiung; Hung, Chung-Feng; Chen, Hsiu-Ling
Abstract: The health effects of non-dioxin like polychlorinated biphenyls (NDL-PCBs) include liver, immune, neurodevelopmental, and neurobehavioral effects in addition to hormone alteration. Among 209 PCB congeners, six indicator PCBs (ICES-6) account for about half of NDL-PCBs present in feed and food. The objectives of the current study were first to examine the levels of total PCBs, NDL-PCBs, and ICES-6 PCBs in 200 foods commonly consumed in Taiwan and, second, to estimate the cumulative health risks of NDL-PCB consumption. We suggest a risk management strategy that identifies foodstuffs with particularly high NDL-PCB content. In 200 food samples, which were grouped into 12 categories and 64 food types, 51 PCB congeners were detected. The concentrations of ICES-6 PCBs in all samples were lower than the maximum levels for NDL-PCBs in foodstuffs set by the European Union. PCB-153, PCB-138, and PCB-180 were the major congeners in all food, indicating that the food was contaminated in the past. ICES-6 PCBs contributed 42.2%–52.9% of total NDL-PCBs in all tested foodstuffs. The average estimated daily intake (EDI) of PCBs ranged from 1.22 ng/kg bw/day to 2.89 ng/kg bw/day in different age groups (95th quantile [P95]: 4.12–10.28 ng/kg bw/day). The P95 EDI in 3–6-year-olds was higher than 10 ng/kg/day. A qualitative sensitivity analysis in ICES-6 PCBs exposure showed that for the 3- to 6-year-old group, the highest sensitivity was how much fish they ate (37.6%) and its concentration (32.5%). The consumption of pork, eggs, fish, and other seafood accounts for over 90% of ICES-6 PCBs intake, and these foods should be highlighted in guidelines regarding NDL-PCB intake. Graphical abstract: Image 1 Highlights: DL-PCBs, NDL-PCBs were detected in 200 foodstuffs. The highest level of NDL-PCBs was in fish, seafood, and livestock. The consumption of pork, eggs, fish, and other seafood accounts for over 90% of NDL-PCBs intake. Except for 3–6-year-olds, current dietary exposure to NDL-PCBs is not a serious health concern.